2009
DOI: 10.1109/tuffc.2009.1227
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of the Ferroelectric Potassium Nitrate: Poly(vinyl alcohol) Composite Films

Abstract: The composite films of ferroelectric potassium nitrate (KNO3):poly(vinyl alcohol) (PVA) with different weight percentages of KNO3 have been prepared at 200 degrees C using the spray-deposition technique. The remanent polarization (Pr) and peak current density for all composite films was estimated by tracing the polarization-electric field (P-E) hysteresis loop and current density-electric field (J-E) loop, respectively, using a modified Sawyer-Tower circuit. Pure KNO3 is known not to exhibit any ferroelectrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…It has been reported that thin films deposited on the different metal substrates shows excellent ferroelectric, electrical, and dielectric properties. 12 17 18 20 The composite films were annealed in vacuum at their deposition temperatures for 24 h and then slowly cooled to room temperature. Indium electrodes with different cross-sectional areas were deposited by thermal evaporation under the vacuum 2 0 × 10 −5 mbar onto the upper surface of the sample.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that thin films deposited on the different metal substrates shows excellent ferroelectric, electrical, and dielectric properties. 12 17 18 20 The composite films were annealed in vacuum at their deposition temperatures for 24 h and then slowly cooled to room temperature. Indium electrodes with different cross-sectional areas were deposited by thermal evaporation under the vacuum 2 0 × 10 −5 mbar onto the upper surface of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…The crystallite size was determined using Scherrer relation. 12 It was found to increase with the deposition temperature. The crystallite size seems to play an important role in the stabilization of ferroelectric phase III in the composite films at room temperature.…”
Section: Articlementioning
confidence: 97%
See 3 more Smart Citations